Les défis de la gouvernance pour concilier protection et valorisation territoriales d’une ressource. Le cas du programme « Agriculture et zones humides » du Parc naturel régional Scarpe-Escaut - Lucie Morère; Éric Glon (Développement Durable et Territoires)
Wet grasslands take shape in nature and through human action. They are at the heart of environmental conflicts and economic challenges. What is at stake in this article is a specific program, “Agriculture and wetlands” that is dealing with these different issues in the Scarpe Escaut Natural regional Park (in the north of France) to find a balance between a viable cattle farming and the preservation of the wetland ecosystem. This huge challenge raises the question of territorial governance and obstacles to reach a compromise between stakeholders who have different interests and different goals. On the one hand, this paper is underlining these difficulties and on the other one, it’s sketching out some territorial opportunities.